Beyond Police Compliance With Electronic Recording of Interrogation Legislation: Toward Error Reduction: - Zalman, Marvin (Criminal justice policy review, 2019)
Video recording police interrogations is a widespread reform designed to reduce false confessions. An exploratory survey of Michigan police departments following the adoption of a video recording law indicates that the policy is uniformly followed. A significant number of agencies go beyond the law’s requirements by video recording in the investigation of all crimes and not only major felonies. Most recording captures both the interrogator and suspect. Prior to passage, half of the agencies supported the law and half were neutral. The law stimulated a quarter of the agencies to video record interrogations. A literature review and policy analysis suggests that video recording is a necessary but not a sufficient reform to reduce false confessions and wrongful convictions. Progress toward less confrontational investigative interviewing, used in several European countries and gaining a foothold in the United States, is recommended.